Functional Outcome of Arthroscopic Debridement of Mucoid Degeneration of the Anterior Cruciate Ligament - Hamal, Bhadra; Karmacharya, Mahesh; Mangal Joshi, Kuldeep; Gorkhali, Rajendra (Journal of Nepal Health Research Council, 2022)
Background: Mucoid degeneration of the anterior cruciate ligament is a rare pathological condition. This is a condition where the anterior cruciate ligament becomes bulky and seems like a celery stalk appearance. The most common symptom is a pain in the posterior aspect of the knee and consistent clinical finding is a mechanical block to an extension of the knee. This study aims to find out the functional outcome of arthroscopic debridement of this entity.Methods: This is a prospective observational study from Jan 1st 2021 to Dec 31st 2021 done in 17 patients. The outcome was measured in terms of preoperative and postoperative visual analogue scale, Tegner Lysholm score and International Knee Documentation Committee score.Results: Eleven females and six males were included in this study. The mean age of the patients was 51.41 years. Arthroscopic debridement of mucoid degeneration of the anterior cruciate ligament was done. Preoperative and 6 months postoperative VAS score was 8.12 and 2.00 respectively (p<0.05), preoperative and 6 months postoperative Tegner Lysholm score was 44.00 and 86.29 respectively (p<0.05), and preoperative and 6 months postoperative IKDC score was 29.06 and 79.94 respectively (p<0.05)Conclusions: Arthroscopic debridement serves as an effective way of treatment of mucoid degeneration of the anterior cruciate ligament.Keywords: Anterior cruciate ligament; arthroscopic debridement; mucoid degeneration.